Probiotic Bacillus pumilus LV149 enhances gut repair, modulates microbiota, and alters transcriptome in DSS-induced colitis mice - Sun, Xinyu; Yun, Long; Xie, Keming; Liu, Renhui; Ren, Xinyue; Zeng, Bokun; Cao, Xudong; Li, Zhi; Zhou, Guihao; Liu, Bang; Peng, Luo; Yuan, Lihong (Frontiers in Microbiology, 2025)
PurposeGut microbiota dysbiosis significantly impacts ulcerative colitis (UC) progression and exacerbation. Probiotics show promise in UC management. This study evaluated the effects of different doses of Bacillus pumilus LV149, an aquatic-derived probiotic, on gut injury repair in male C57BL/6 mice with dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) and investigated the underlying mechanisms.MethodsUC was induced by allowing mice free access to a 3% DSS solution for 7 days, with concurrent daily oral gavage of either a low (LV149-L, 1 × 108 CFU/day/mouse) or high (LV149-H, 1 × 109 CFU/day/mouse) dose of LV149. The effects were assessed through physiological parameters, intestinal barrier integrity, inflammation, gut microbiota composition, and transcriptomic changes.ResultsLV149 significantly improved pathological symptoms, including weight loss and disease activity index (DAI), and reduced colon shortening in a dose-dependent manner and inflammatory damage. The intervention also restored gut barrier function by upregulating mucins, goblet cell counts, and tight junction proteins (ZO-1, occludin, and claudin-1) in colonic tissue, along with reducing serum lipopolysaccharide (LPS) levels. Notably, only the LV149-H significantly decreased the expression of pro-inflammatory cytokines TNF-α, IL-1β, and IL-6, while both doses increased the expression of the anti-inflammatory cytokine IL-10 in a dose-dependent in colonic tissue. LV149 further modulated the gut microbiota, increasing beneficial bacteria and reducing pathogenic populations. Transcriptomic analysis indicated that LV149-L may exert gut repair effects via the IL-17 signaling pathway, whereas LV149-H appears to act through the JAK-STAT signaling pathway.ConclusionThis study demonstrated that LV149, particularly at a higher dose, effectively mitigated DSS-induced colonic injury by modulating gut microbiota, enhancing gut barrier integrity, and reducing inflammation. The dose-dependent effects underscored LV149-H’s potential as a therapeutic agent for UC due to its stronger anti-inflammatory properties and gut-protective effects.